A Semantics Analysis of “Massure” Poetry By Muskamal Bare in City of Bone, South Sulawesi - Hariratul Jannah; Sumirna Sumirna; Firdayanti Firdayanti (Tamaddun Life, 2016)
The research aims are to find out the concept of semantics constructed in the “ Massure” poetry and to find out the meaning of “Massure” poetry by Muskamal Bare in city of Bone, South Sulawesi. In this study, the writer used descriptive qualitative method to analyzed data. The writer observed the location, interviewed to the author and some people in Bone, South Sulawesi , and used some tools as documentation which relate to the research in Bone, South Sulawesi.“Massure“ poetry has a lexical meaning and grammatical meaning. Lexical meaning that is the meaning of each word and grammatical meaning that is the meaning of each sentence. So there are differences among lexical and grammatical meaning that contained in “ Massure” poetry by Muskamal Bare in Bone , South Sulawesi.“ Massure “ is the delivery or coveying a story Either it is about the kingdom ,hero, natural disasters and etc. In this poetry talking about customs in the kingdom of Bone. Anyone who violates customs as good as he makes all people angry and been a disaster by many people.